Muṣṭalaḥāt Tanāṣiyyah baina al-Aṣālah wa al-Ĥadāśah - Ahmad, Nazifi Shehu; Farouq, Aminu Umar (Aphorisme: Journal of Arabic Language, Literature, and Education, 2023)
The term intertextuality is a modern term for an ancient phenomenon represented in rhetorical phenomena, such as: quotation, theft, embedding, and others. It is a phenomenon that represents an important aspect of modern criticism, and therefore the researcher tried to provide a model of its definitions and the contrast that occurs between it and rhetorical terms. This research aims to show the relationship that exists between the term intertextuality and rhetorical terms, and the extent of agreement and difference between them, by tracking it through study and analysis, to make it easier for the recipient to savor it, clarify its values, and highlight the artistic creativity inherent in it. The importance of this research is evident in monitoring how the reader benefits from new terms, in addition to the literary terms he knew before. It also reveals the extent of poets’ ingenuity in using the literary heritage to deepen the structural and semantic connotations of their poetry.